Please tick the appropriate box: Perspectives on patient reported experience - Mette Sandager (The Beryl Institute, 2016)
Patient experience surveys are increasingly used as a method for evaluating important aspects of quality of care and the results are used politically to support general decision-making. However, there have been limited attempts to summarize the newest and most essential knowledge on how to measure and interpret patient experience data. This paper aims to summarize knowledge on the association between delivered care and patient reported experience and the factors influencing this association, and to outline a conceptual model illustrating the association. The method employed is integrative literature review. Quantitative and qualitative studies as well as theoretical and discussion papers that specifically related to the concept of patient evaluations were included. Identified literature was scoped. Thematic analysis was conducted and the results were used to synthesize a model by integrating identified factors. Expectations, patient characteristics, survey timing, loyalty to health professionals, backing up own choices and questionnaire and item design where identified as factors influencing the association between delivered care and patient reported experience. The developed model suggests that there should be a clear differentiation between patient’s experience and patient reported experience. The model derived from the literature underlines that the association between received care and patient reported experience is complex. Patient reported experience data should be interpreted with caution, as reported positive experiences might neither reflect high quality care nor satisfied patients.